The state of cropland nitrous oxide emission research in Sub-Saharan Africa - Ouma, Turry; Barthel, Matti; Agredazywczuk, Phillip; Tufail, Muhammad A.; Zerssa, Gebeyanesh W.; Gebremichael, Haftu B.; Leitner, Sonja M.; Oduor, Collins; Ntinyari, Winnie; Oluoch, Kevin C.; Otinga, Abigael; Njoroge, Ruth; et al. (Frontiers in Environmental Science, 2026)
Nitrous oxide (N2O) emissions from cropland soils are a significant source of greenhouse gases in Sub-Saharan Africa (SSA), yet fluxes and drivers remain poorly quantified. This review synthesizes findings from 39 field-based studies across Sub-Saharan Africa to assess current knowledge, key drivers, and research gaps. Additionally, this review offers a focused analysis on the effect of nitrogen fertilizer application on N2O emissions. The main finding is that emissions were strongly influenced by nitrogen input rates, precipitation, cropping systems, soil types, and measurement durations. Emission factors often diverge from IPCC Tier 1 defaults, suggesting the need for context-specific values. However, research is unevenly distributed: Studies from Kenya dominate the literature, while large areas, especially in Central Africa, lack data. Methodological inconsistencies further limit comparability across studies. We identify priorities for future research, including geographic expansion, standardized protocols, and improved integration of climate and agronomic variables. Strengthening the regional evidence base is essential for accurate inventories and for developing climate-smart agricultural policies tailored to SSA’s diverse agroecosystems.